The effectiveness of a proposed program according to the constructivist theory to develop spatial ability in geography (Journal of the College of Basic Education, 2022)
The current research aims to:1. Building an educational program according to the constructivist theory to develop spatial ability in geography.2. Recognizing the effectiveness of the proposed program according to the constructivist theory for the development of spatial ability in the subject of geography.To achieve the aims of the research, the researchers formulated the following hypothesis:1. There is no statistically significant difference at the level (0.05) between the mean scores of the students of the experimental group who study the subject of geography in the proposed program and the mean scores of the students of the control group who study the same subject in the traditional way in the post spatial ability test.